Deficiency of employability capacity - Pelse I.; Vilka L. (SHS Web of Conferences, 2012)
Young unemployed people have comprised one of the significantly largest groups of the unemployed people in Latvia in recent years. One of the reasons why young people have difficulty integrating into the labour market is the “expectation gap” that exists in the relations between employers and the new generation of workers. Employers focus on capacity-building for employability such individual factors as strength, patience, self-discipline, self-reliance, self-motivation, etc., which having a nature of habit and are developed in a long-term work socialization process, which begins even before the formal education and will continue throughout the life cycle. However, when the socialization is lost, these habits are depreciated faster than they can be restored. Currently a new generation is entering the labour market, which is missing the succession of work socialization. Factors, such as rising unemployment and poverty in the background over the past twenty years in Latvia have created a very unfavourable employability background of “personal circumstances” and “external factors”, which seriously have impaired formation of the skills and attitudes in a real work environment. The study reveals another paradox – the paradox of poverty. Common sense would want to argue that poverty can be overcome by the job. However, the real state of affairs shows that unfavourable coincidence of the individual, personal circumstances and external factors leads to deficit of employability capacity and possibility of marked social and employment deprivation.